Cornstarch-coated activated carbon as a novel adsorbent for efficient detection of human norovirus in coastal shellfish - Ningbo Liao; Lu Ruan; Chengwei Liu; Yuexia Wang; Peng Tian; Ronghua Zhang; Guoping Wu (Food Control, 2026)

Hierarchical Core-sheath breathable textiles with absorption-dominated EMI shielding, strain-insensitive conductivity and efficient joule heating - Jian Zhang; Shasha Wang; Fengkai Zhou; Danna Zhou; Ziyue Zhu; Leqian Wei; Liqi Zhou; Mengqi Shan; Qian Zhang; Meiqi Hu; Guoping Guan; Fujun Wang; et al. (Chemical Engineering Journal, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

Effects of Lactiplantibacillus plantarum fermentation on the flavor profile and in vitro digestive characteristics of easy-to-swallow surimi gels - Fei Wang; Xinyu Liu; Yao Wang; Jinping Zhang; Xiaoling Lu; Xiang Li; Xugan Wu; Guoping Zhao; Jing Xie; Xichang Wang; Weiqiang Qiu (Food Chemistry, 2026)

Chemically induced proximity-driven dimerization of split Cas12a enables sensitive rapamycin detection in blood - Zhen Huang; Xiaowen Hu; Yajuan Zhou; Shanshan Zhang; Yao Zhao; Lei Xiong; Xuchun Han; Miaona Liu; Yao Hu; Yizhuo Zhang; Luqin Lv; Qiuxiang Cheng; et al. (Science Bulletin, 2026)

Head-to-head comparison of plasma biomarker assays across platforms for amyloid pathology in a multicenter cohort - Xinyi Lv; Kaiyuan Shen; Qianhua Zhao; Guoping Peng; Huayan Liu; Feng Gao; Xiaodong Pan; Wei Chen; Peilin Lu; Haining Zhang; Shuting Zhang; Mengya Xing; et al. (Science Bulletin, 2026)

Osteoprotective effect of Perinereis aibuhitensis ultrasound-assisted aqueous extract against retinoic acid-induced osteoporosis in mice - Biliang Mo; Xinxia Song; Jianmeng Liao; Xiaoyu Xia; Hongyu Lu; Wenhong Cao; Zhongqin Chen; Mingtang Tan; Huina Zheng; Jialong Gao; Haisheng Lin; Zhihong Zheng; et al. (Food Bioscience, 2026)

Evolution and functional characterization of the MdSKP8 gene as a conserved hub integrating hormone and antioxidant pathways for salt tolerance in apple - Miao Shao; Yongqing Feng; Shixiong Lu; Shangwen Yang; Jian Li; Xinyu Li; Zonghuan Ma; Guoping Liang; Baihong Chen; Juan Mao (Plant Cell Reports, 2026)

Identification of KL29 type acinetobacter baumannii phage of obolenskvirus subfamily and tail-associated depolymerase activity - Jinpan Wei; Tao Yu; Qiang Wang; Can Wang; Xuefeng Li; Guoping Lu; Lijuan Li; Aihui Xu; Lei Zhao (Archives of Virology, 2026)

Crafting cellulose hollow microspheres with cellulose nanosheets - Wenxuan Lei; Heng Huang; Ruobing Liang; Guoping Li; Pan Chen; Jiechun Xiang; Ang Lu (Carbohydrate Polymers, 2026)

Tomographic PIV investigation of the tip-clearance vortex formation and evolution for a hydrofoil - Yuhu Qu; Wenxuan She; Xintao Lu; Pengming Guo; Qi Gao; Guoping Zhang; Xinming Du; Hang Zhao (Ocean Engineering, 2026)

Uncovering the role of Li+-H2O ion-dipole interaction in zeolite deactivation - Chenghao Liu; Yong Li; Zhe Lu; Shuzhuang Sun; Yong Wang; Zhifu Liu; Gang (Kevin) Li; Jingyue Shang; Songbai Hu; Lunhua He; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

VvGA2ox8-Like from grape confers drought tolerance by activating the antioxidant defense system - Wenqi Yang; Juanbo Yang; Shixiong Lu; Huimin Gou; Ning Wang; Miao Yuan; Weifeng Ma; Baozhen Zeng; Guoping Liang; Juan Mao (Plant Cell Reports, 2026)

A 500-year cycle of demographic expansion and contraction in the lower Yangtze and adjacent coastal region during the Holocene driven by East Asian summer monsoon oscillations - Deke Xu; Yuhai Wang; Keyang He; Hao Li; Yajie Dong; Jun Kuang; Zhigang Zhang; Bing Song; Yulong Niu; Guoping Sun; Yonglei Wang; Jiatong Lu; et al. (Quaternary Science Reviews, 2026)

Impact of Monascus purpureus fermentation on the gel properties of Alaska Pollock surimi: Dysphagia-oriented foods - Xinyu Liu; Fei Wang; Yao Wang; Jinping Zhang; Xiaoling Lu; Xugan Wu; Guoping Zhao; Jing Xie; Weiqiang Qiu (Food Chemistry, 2026)

Five daucane-type sesquiterpenes isolated from the roots of Ferula songarica Pall. ex Schult. and their anti-gastric cancer activity - Xiaotong Chang; Guoping Wang; Degang Qing; Yu Sun; Yaqin Zhao; Ning Lu; Leiling Shi; Jie Lv (Natural Product Research, 2026)

Regulation of Melatonin on AQP4 Expression in Brain of SD Newborn Rats with Bilirubin Encephalopathy and Protection Mechanism - Kaige Xue; Xuefeng Cheng; Weijian Qian; Hemant Mistry; Ping Fan; Jiaheng Hu; Chunyan Chen; Lirong Zhang; Parisa Vazirinasab; Juan Huang; Weitian Lu; Jin Xu; et al. (Molecular Neurobiology, 2026)

Distinguished behaviors between stream CO2 and CH4 concentrations and the potential causes in a headwater catchment of southern China - Nan Jiang; Guoping Tang; Wenya Zhang; Houbing Chen; Xupeng Fang; Zhongkai Ren; Xixi Lu (Journal of Hydrology, 2025)

A 5-year field study to assess interannual variability and determinants of cotton fiber quality in intercropping systems - Haoyue Qin; Yurui Tang; Xin Li; Yurong Qiu; Jian Wang; Yingchun Han; Guoping Wang; Shiwu Xiong; Minghua Xin; Wenli Du; Lu Feng; Yongjiang Zhang; et al. (European Journal of Agronomy, 2025)

A flexible microneedle sensor for long-term, enzyme-free glucose monitoring with high sensitivity and stability - Ying Liu; Zhen Lei; Congcong Ren; Jifu Mao; Fan Zhao; Lu Wang; Guoping Guan (Analytica Chimica Acta, 2025)

Co-transport behavior of aged polymeric methyl methacrylate nanoplastics and florfenicol antibiotic in porous media: Effects of electrolyte, pH, and aging duration - Lihui Tan; Ming Wu; Yanru Hao; Hui Li; Cehui Mo; Guoping Lu (Water Research, 2025)

Hydrochemical characteristics of carbonated waters and non-carbonated thermal waters of the Heyuan Deep Fault Zone in Guangdong, Southern China - Xianxing Huang; Linjun Xie; Yan Li; Guoping Lu (Geothermics, 2025)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Fault detection based on U-Net and GNN integration - Guoqing Lu; Lianbo Zeng; Guoping Liu; Jian Su; José Luis Drummond Alves; Junfeng Zhao; Mehdi Ostadhassan (Journal of Structural Geology, 2025)

Polyvalent immunoprotection of protein, DNA and IgY antibody vaccines of Vibrio fluvialis outer membrane protein VF08100 in fish - Huihui Xiao; Saixing Duan; Pan Cui; Jing Chen; Xixian Che; Juan Lu; Juan Wang; Guoping Zhu; Yong Liu; Xiang Liu (Fish & Shellfish Immunology, 2025)

Trans-scale Evaluation of Strengthening of a Shale by Injecting Oil- and Water-Based Nanoparticle Suspensions - Yongkang Wu; Yucheng Li; Shengmin Luo; Meng Lu; Nancy Zhou; Yuanzhi Qu; Yuan Geng; Guoping Zhang (Rock Mechanics and Rock Engineering, 2025)

High instantaneous response quartz crystal microbalance humidity sensor for respiratory droplet detection - Jiaqi Lu; Xiangdong Chen; Xing Ding; Zhuolin Jia; Mengxi Zhang; Xiang Yu; Kun Tang; Fang Liu; Hui Li; Guoping Li (Chemical Engineering Journal, 2025)

Synthetic bacterial communities regulate polyamine metabolism and genes encoding antioxidant defense system to enhance arsenic tolerance of rice - Hamad Khan; Zeeshan Khan; Ishmal Eman; Ijaz Ahmad; Tariq Shah; Guoping Wang; Lu Feng; Abdullah A. Alarfaj; Sulaiman Ali Alharbi; Muhammad Javed Ansari (South African Journal of Botany, 2025)

Peanut–cotton intercropping to enhance soil ecosystem multifunctionality: Roles of microbial keystone taxa, assembly processes, and C-cycling profiles - Shijie Zhang; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Shiwu Xiong; Beifang Yang; Xiaoyu Zhi; Minghua Xin; Yahui Jiao; Xiao-Fei Li; Yabing Li; et al. (Agriculture, Ecosystems & Environment, 2025)

Transport behavior of Polymeric Methyl Methacrylate nanoplastics in saturated and unsaturated porous media: Combined influence of electrolyte and organic acids - Lihui Tan; Lulu Ding; Ming Wu; Zhou Cheng; Yanru Hao; Guoping Lu (Journal of Environmental Chemical Engineering, 2024)

Instantaneous detection and location of contaminant sources in intelligent buildings: A distributed Kalman filter scheme - Chen Ma; Aibing Qiu; Xiaojing Peng; Juping Gu; Guoping Lu (Energy and Buildings, 2024)

Genome-wide identification of Aux/IAA gene family members in grape and functional analysis of VaIAA3 in response to cold stress - Shixiong Lu; Min Li; Yongjuan Cheng; Huimin Gou; Lili Che; Guoping Liang; Juan Mao (Plant Cell Reports, 2024)

Impact of diatomit on the transport behavior of unmodified and carboxyl-modified nanoplastics in saturated porous media - Yuheng Wu; Ming Wu; Zhou Cheng; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu; Guoping Lu (Environmental Pollution, 2024)

Bedding-parallel fracture density prediction using graph convolutional network in continental shale oil reservoirs: A case study in Mahu Sag, Junggar basin, China - Guoqing Lu; Lianbo Zeng; Guoping Liu; Xiaoxuan Chen; Mehdi Ostadhassan; Xiaoyu Du; Yangkang Chen (Marine and Petroleum Geology, 2024)

AcrAB-TolC efflux pump overexpression and tet(A) gene mutation increase tigecycline resistance in Klebsiella pneumoniae - Zhaoxin Xia; Jing zhou; Nana Gao; Ge Li; Runde Liu; Guoping Lu; Jilu Shen (World Journal of Microbiology and Biotechnology, 2024)

Estimation of groundwater-level changes based on GRACE satellite and GLDAS assimilation data in the Songnen Plain, China - Jinliang Zhang; Zhong Lu; Chaoqun Li; Guoping Lei; Ziyang Yu; Kuo Li (Hydrogeology Journal, 2024)

Correction of linear fracture density and error analysis using underground borehole data - Dongsheng Cao; Lianbo Zeng; Enrique Gomez-Rivas; Lei Gong; Guoping Liu; Guoqing Lu; Paul D. Bons (Journal of Structural Geology, 2024)

Significance of non-DLVO interactions on the co-transport of levofloxacin and titanium dioxide nanoparticles in porous media - Yiqun Cui; Ming Wu; Guoping Lu; Zhou Cheng; Meng Chen; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Environmental Pollution, 2024)

Integrated Metagenomics and 15N Isotope Tracing Reveal the Mechanisms Through which the Nitrogen-Planting Density Interaction Impacts Rice Root Nitrogen Uptake Efficiency - Changhui Sun; Yanyao Lu; Guoping Tang; Runnan Wang; Han Wu; Jiao Zhang; Shuo Cai; Jinyan Zhu; Qiangqiang Xiong (Journal of Soil Science and Plant Nutrition, 2024)

Grapefruit essential oil combined with UV-C treatment: A technology to improve the microbial safety of fresh produce - Ningbo Liao; Xinyun Chen; Mengxuan Tang; Peng Tian; Chengwei Liu; Lu Ruan; Hong Pan; Mei Shu; Chan Zhong; Guoping Wu (Innovative Food Science & Emerging Technologies, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

CO2 capture using low silica X zeolite synthesized from low-grade coal gangue via a two-step activation method - Chenghao Liu; Fu Rao; Yalou Guo; Zhe Lu; Wenkang Deng; Guobiao Li; Hui Zhang; Tao Qi; Guoping Hu (Journal of Environmental Chemical Engineering, 2024)

Establishing a pulmonary aspergillus fumigatus infection diagnostic platform based on RPA-CRISPR-Cas12a - Chunhui Lin; Jing Zhou; Nana Gao; Runde Liu; Ge Li; Jinyu Wang; Guoping Lu; Jilu Shen (World Journal of Microbiology and Biotechnology, 2024)

Quantifying physiological contributions to yield loss in response to planting date in short-season cotton under a cotton wheat double-cropping system - Simeng Guo; Yingchun Han; Guoping Wang; Fengqi Wu; Yaoyu Jia; Jiale Chen; Xiaofei Li; Wenli Du; Yabing Li; Lu Feng (European Journal of Agronomy, 2024)

Geographic mosaics of rice domestication in the lower Yangtze River indicated by morphological characteristics of rice bulliform phytoliths - Keyang He; Yonglei Wang; Yunfei Zheng; Guoping Sun; Shao Lei; Yongning Li; Xiaoshan Yu; Jianping Zhang; Houyuan Lu (Archaeological and Anthropological Sciences, 2024)

Quantification and visualization of groundwater contamination prevention regionalization based on analytic hierarchy process method (AHP) in Guangdong-Hong Kong-Macao Greater Bay Area, South China - Zhou Cheng; Guoping Lu; Ming Wu; Zhaohui Li; Yirong Deng; Jinzhe Wu; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Journal of Hydrology, 2024)

Explaining nitrogen turnover in sediments and water through variations in microbial community composition and potential function - Shan Yang; Meijun Dong; Huibin Lu; Zhipeng Cai; Meng Ge; Jia Xing; Haobin Huang; Youda Huang; Guoping Sun; Shaofeng Zhou; Meiying Xu (Chemosphere, 2023)

Mechanisms influencing changes in water cycle processes in the changing environment of the Songnen Plain, China - Zhong Lu; Kuo Li; Jinliang Zhang; Guoping Lei; Ziyang Yu; Chaoqun Li (Science of The Total Environment, 2023)

Attribution of vegetation fluorescence changes in China based on a decision tree stratification strategy - Ziyang Yu; Zhong Lu; Yiyang Guo; Ying Zhang; Guoping Lei (Advances in Space Research, 2023)

Formation of natural fractures and their impact on shale oil accumulation in the Mahu Sag, Junggar Basin, NW China - Xiaoyu Du; Zhijun Jin; Lianbo Zeng; Guoping Liu; Wenjun He; Mehdi Ostadhassan; Yong Song; Xinping Liang; Sen Yang; Guoqing Lu (International Journal of Coal Geology, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Quantification of two-site kinetic transport parameters of polystyrene nanoplastics in porous media - Yuheng Wu; Zhou Cheng; Ming Wu; Yanru Hao; Guoping Lu; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Chemosphere, 2023)

Characteristics and controlling factors of natural fractures in deep lacustrine shale oil reservoirs of the Permian Fengcheng Formation in the Mahu Sag, Junggar Basin, China - Xiaoyu Du; Zhijun Jin; Lianbo Zeng; Guoping Liu; Wenjun He; Mehdi Ostadhassan; XinPing Liang; Sen Yang; Guoqing Lu (Journal of Structural Geology, 2023)

Natural fractures in deep continental shale oil reservoirs: A case study from the Permian Lucaogou formation in the Eastern Junggar Basin, Northwest China - Guoping Liu; Zhijun Jin; Lianbo Zeng; Liliang Huang; Mehdi Ostadhassan; Xiaoyu Du; Guoqing Lu; Yunzhao Zhang (Journal of Structural Geology, 2023)

Growing cover crop mixtures are more sustainable than single cover crop in continuous cotton cropping: Comprehensive assessment from 3-year field experiment - Zhenggui Zhang; Jian Wang; Weibin Huang; Yingchun Han; Guoping Wang; Lu Feng; Xiaofei Li; Shiwu Xiong; Minghua Xin; Yabing Li; Zhanbiao Wang (Journal of Cleaner Production, 2023)

Assessing Spatio-Temporal Variability of Soil Phosphorus in Different Cotton-Based Cropping Systems Using Geo-Statistics - Li Teng; Xiong Shiwu; Wang Zhanbao; Li Xiaofei; Han Yingchun; Wang Guoping; Lei Yaping; Feng Lu; Yang Beifang; Zhi Xiaoyu; Fan Zhengyi; Li Yabing (Journal of Soil Science and Plant Nutrition, 2023)

Correction to: Molecular characterization of a novel amalgavirus infecting lilium spp. in China - Zhihao Yuan; Zhenfeng Li; Yuexia Lu; Mengji Cao; Ni Hong; Guoping Wang; Li Cai (Archives of Virology, 2023)

Optimizing plant type structure to adjust the temporal and spatial distribution of water consumption and promote the growth and yield formation of cotton - Yaru Wang; Jiale Chen; Fengqi Wu; Beifang Yang; Yingchun Han; Lu Feng; Zhanbiao Wang; Xiaofei Li; Yaping Lei; Shiwu Xiong; Guoping Wang; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Molecular characterization of a novel amalgavirus infecting lilium spp. in China - Zhihao Yuan; Zhenfeng Li; Yuexia Lu; Mengji Cao; Ni Hong; Guoping Wang; Li Cai (Archives of Virology, 2023)

Important effects of polypropylene on migration of ciprofloxacin in groundwater - Yanna Chen; Cehui Mo; Ming Wu; Yanru Hao; Zhou Cheng; Guoping Lu; Qusheng Li; Bill X. Hu; Jianfeng Wu; Jichun Wu (Journal of Environmental Chemical Engineering, 2023)

The Lnc-HOTAIR/miR122/PPARγ signaling mediated the occurrence and continuous development of alcohol-induced Osteonecrosis of the femoral head - Guoping Le; Mengting Lu; Li Li; Hanwen Luo (Toxicology Letters, 2023)

The nitrogen footprint and reactive nitrogen reduction potential of cotton production in China - Weibin Huang; Fengqi Wu; Zhenggui Zhang; Yongming Meng; Jian Wang; Qinqin Li; Yingchun Han; Lu Feng; Xiaofei Li; Guoping Wang; Yaping Lei; Zhengyi Fan; et al. (Journal of Cleaner Production, 2023)

Lithology identification using graph neural network in continental shale oil reservoirs: A case study in Mahu Sag, Junggar Basin, Western China - Guoqing Lu; Lianbo Zeng; Shaoqun Dong; Liliang Huang; Guoping Liu; Mehdi Ostadhassan; Wenjun He; Xiaoyu Du; Chengpeng Bao (Marine and Petroleum Geology, 2023)

Use of bentonite-coated activated carbon for improving the sensitivity of RT-qPCR detection of norovirus from vegetables and fruits: The ISO 15216-1:2017 standard method extension - Mengxuan Tang; Ningbo Liao; Peng Tian; Kaisheng Shen; Chengwei Liu; Lu Ruan; Guoping Wu (Food Microbiology, 2023)

Climate warming accelerates cotton growth while cultivar shifts extend the growth period - Wanrui Han; Shengli Liu; Yaping Lei; Yongjiang Zhang; Yingchun Han; Guoping Wang; Lu Feng; Xiaofei Li; Yabing Li; Zhanbiao Wang (Field Crops Research, 2023)

Changes in within-boll yield components explain cotton yield and quality variation across planting dates under a double cropping system of cotton-wheat - Simeng Guo; Taijie Liu; Yingchun Han; Guoping Wang; Wenli Du; Fengqi Wu; Yabing Li; Lu Feng (Field Crops Research, 2023)

VaSUS2 confers cold tolerance in transgenic tomato and Arabidopsis by regulation of sucrose metabolism and ROS homeostasis - Yanmei Li; Guoping Liang; Guojie Nai; Shixiong Lu; Weifeng Ma; Zonghuan Ma; Juan Mao; Baihong Chen (Plant Cell Reports, 2023)

Orychophragmus violaceus/cotton relay intercropping with reduced N application maintains or improves crop productivity and soil carbon and nitrogen fractions - Zhenggui Zhang; Jian Wang; Shiwu Xiong; Weibin Huang; Xiaofei Li; Minghua Xin; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Beifang Yang; Yabing Li; et al. (Field Crops Research, 2023)

Quantitative evaluation of variation and driving factors of the regional water footprint for cotton production in China - Qinqin Li; Weibin Huang; Jian Wang; Zhenggui Zhang; Yabing Li; Yingchun Han; Lu Feng; Xiaofei Li; Beifang Yang; Guoping Wang; Yaping Lei; Shiwu Xiong; et al. (Sustainable Production and Consumption, 2023)

Ratiometric fluorescent sensing of phosphate ion in environmental water samples using flavin mononucleotide-functionalized Fe3O4 particles - Fang Xu; Wei Leng; Qinwei Lu; Kunpeng Li; Yukuai Zhang; Jingyu Liu; Liqiang Xu; Guoping Sheng (Science of The Total Environment, 2023)

Identification and expression analysis of the grape pentatricopeptide repeat (PPR) gene family in abiotic stress - Lili Che; Shixiong Lu; Guoping Liang; Huimin Gou; Min Li; Baihong Chen; Juan Mao (Physiology and Molecular Biology of Plants, 2022)

Temperature-phase transcriptomics reveals that hormones and sugars in the phloem of grape participate in tolerance during cold acclimation - Guoping Liang; Zonghuan Ma; Shixiong Lu; Weifeng Ma; Lidan Feng; Juan Mao; Baihong Chen (Plant Cell Reports, 2022)

An integrated analysis of single-cell and bulk transcriptomics reveals EFNA1 as a novel prognostic biomarker for cervical cancer - Xiaopeng Shen; Meng Li; Yang Lei; Shan Lu; Sufen Wang; Zhongxian Liu; Chunguang Wang; Yun Zhao; Ao Wang; Chao Bi; Guoping Zhu (Human Cell, 2022)

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

On the origin of SARS-CoV-2—The blind watchmaker argument - Chung-I Wu; Haijun Wen; Jian Lu; Xiao-dong Su; Alice C. Hughes; Weiwei Zhai; Chen Chen; Hua Chen; Mingkun Li; Shuhui Song; Zhaohui Qian; Qihui Wang; et al. (Science China Life Sciences, 2021)

Multi-proxy evidence of environmental change related to collapse of the Liangzhu Culture in the Yangtze Delta, China - Keyang He; Houyuan Lu; Guoping Sun; Xiang Ji; Yonglei Wang; Kaikai Yan; Xinxin Zuo; Jiangping Zhang; Bin Liu; Ningyuan Wang (Science China Earth Sciences, 2021)

Study of the geostatistical grid maths operation method of quantifying water movement in soil layers of a cotton field * - Liyuan Liu; Fangfang Xing; Yabing Li; Yingchun Han; Zhanbiao Wang; Xiaoyu Zhi; Guoping Wang; Lu Feng; Beifang Yang; Yaping Lei; Zhengyi Fan; Wenli Du (Irrigation and Drainage, 2020)
The precise quantification of water movement in different field soil layers is important for variable‐rate irrigation and fertilization. To this end, a field experiment based on a geostatistical approach was conducted in southern Anyang, Henan, China, to examine soil water movement in a cotton field with drip irrigation by measuring the soil water content (SWC) data on a regular 100 × 80 cm grid. The result shows that the temporal and spatial variation of soil moisture decreased with the increase of soil depth at different points, and apparent spatial heterogeneity was observed under different soil conditions through a semivariogram analysis. The variation of soil moisture at different soil profiles was affected by the cotton plants and drip lines in non‐irrigation and irrigation periods respectively. The level of the change at 20 cm was more than 70 cm in the horizontal direction in the two periods, however the degree of change at 40 cm in the irrigation period was more than 70 cm in the vertical direction, while contrary results were shown in the non‐irrigation period. Moreover, the results indicated that the trapezoidal rule could be applied to quantify the volume of water movement precisely.

Optimized trio genome sequencing (OTGS) as a first-tier genetic test in critically ill infants: practice in China - Huijun Wang; Yulan Lu; Xinran Dong; Guoping Lu; Guoqiang Cheng; Yanyan Qian; Qi Ni; Ping Zhang; Lin Yang; Bingbing Wu; Wenhao Zhou (Human Genetics, 2020)

Characterization of Shale Softening by Large Volume-Based Nanoindentation - Yunhu Lu; Yucheng Li; Yongkang Wu; Shengmin Luo; Yan Jin; Guoping Zhang (Rock Mechanics and Rock Engineering, 2020)

N-(3-oxo-acyl) homoserine lactone induced germ cell apoptosis and suppressed the over-activated RAS/MAPK tumorigenesis via mitochondrial-dependent ROS in C. elegans - Bin Chen; Xianbin Cao; Huayi Lu; Pengbo Wen; Xiaojing Qi; Shaopeng Chen; Lijun Wu; Chi Li; An Xu; Guoping Zhao (Apoptosis, 2018)

A Metric Model on Identifying the National Water Scarcity Management Ability - Yue Chen; Guoping Cen; Chuanping Hong; Jiying Liu; Song Lu (Water Resources Management, 2018)

ZIKA virus isolated from mosquitoes: a field and laboratory investigation in China, 2016 - Shihong Fu; Song Song; Hong Liu; Yuanyuan Li; Xiaolong Li; Xiaoyan Gao; Ziqian Xu; Guoping Liu; Dingming Wang; Zhenzao Tian; Jingzhu Zhou; Ying He; et al. (Science China Life Sciences, 2017)

Silencing of SlHB2 Improves Drought, Salt Stress Tolerance, and Induces Stress-Related Gene Expression in Tomato - Jingtao Hu; Guoping Chen; Wencheng Yin; Baolu Cui; Xiaohui Yu; Yu Lu; Zongli Hu (Journal of Plant Growth Regulation, 2017)

Silencing SlAGL6, a tomato AGAMOUS-LIKE6 lineage gene, generates fused sepal and green petal - Xiaohui Yu; Guoping Chen; Xuhu Guo; Yu Lu; Jianling Zhang; Jingtao Hu; Shibing Tian; Zongli Hu (Plant Cell Reports, 2017)

Evaluation of forest structure, biomass and carbon sequestration in subtropical pristine forests of SW China - Syed Moazzam Nizami; Zhang Yiping; Zheng Zheng; Lu Zhiyun; Yang Guoping; Sha Liqing (Environmental Science and Pollution Research, 2017)

Integrated transcriptome analysis of human iPS cells derived from a fragile X syndrome patient during neuronal differentiation - Ping Lu; Xiaolong Chen; Yun Feng; Qiao Zeng; Cizhong Jiang; Xianmin Zhu; Guoping Fan; Zhigang Xue (Science China Life Sciences, 2016)

Investigation of discharge-area groundwaters for recharge source characterization on different scales: the case of Jinan in northern China - Jiale Wang; Menggui Jin; Guoping Lu; Dele Zhang; Fengxin Kang; Baojie Jia (Hydrogeology Journal, 2016)

Aqueous chemistry of typical geothermal springs with deep faults in Xinyi and Fengshun in Guangdong Province, China - Guoping Lu; Runfang Liu (Journal of Earth Science, 2015)

The C161T polymorphism in the peroxisome proliferator-activated receptor gamma gene (PPARγ) is associated with risk of coronary artery disease: a meta-analysis - Zhijun Wu; Yuqing Lou; Wei Jin; Yan Liu; Lin Lu; Guoping Lu (Molecular Biology Reports, 2013)

Senescent endothelial dysfunction is attributed to the up-regulation of sphingosine-1-phosphate receptor-2 in aged rats - Hongwei Lu; Hong Yuan; Shuhua Chen; Lihua Huang; Hong Xiang; Guoping Yang; Hao Deng; Jun Zhou (Molecular and Cellular Biochemistry, 2012)

An ethylene response factor (ERF5) promoting adaptation to drought and salt tolerance in tomato - Yu Pan; Graham B. Seymour; Chungui Lu; Zongli Hu; Xuqing Chen; Guoping Chen (Plant Cell Reports, 2012)

A potential flood hazard caused by Tianchi volcano eruption in Changbai Mountain, Northeast China - Kunshan Bao; Guoping Wang; Xianguo Lu; Neil B. McLaughlin (Journal of Mountain Science, 2011)

Functional analysis of tomato LeEIL1 in an Arabidopsis ein2 mutant - Yu Pan; Guoping Chen; Chungui Lu; Xuqing Chen; Zongli Hu (Acta Physiologiae Plantarum, 2011)

Grain-size characteristics of sediment in Daniugou peatland in Changbai Mountains, Northeast China: Implications for atmospheric dust deposition - Kunshan Bao; Lin Jia; Xianguo Lu; Guoping Wang (Chinese Geographical Science, 2010)

Effects of Pipeline Construction on Wetland Ecosystems: Russia–China Oil Pipeline Project (Mohe-Daqing Section) - Xiaofei Yu; Guoping Wang; Yuanchun Zou; Qiang Wang; Hongmei Zhao; Xianguo Lu (Ambio, 2010)

Freeze-thaw effects on sorption/desorption of dissolved organic carbon in wetland soils - Xiaofei Yu; Yuxia Zhang; Hongmei Zhao; Xianguo Lu; Guoping Wang (Chinese Geographical Science, 2010)

Sodium butyrate-induced upregulation of p18 INK4C gene affects K562 cell G0/G1 arrest and differentiation - Lin Li; Guoping Zhang; Ye Zhang; Jiang Tan; Hui Huang; Baiqu Huang; Jun Lu (Molecular and Cellular Biochemistry, 2008)

Multiple component end-member mixing model of dilution: hydrochemical effects of construction water at Yucca Mountain, Nevada, USA - Guoping Lu; Eric L. Sonnenthal; Gudmundur S. Bodvarsson (Hydrogeology Journal, 2008)

Analyzing unsaturated flow patterns in fractured rock using an integrated modeling approach - Yu-Shu Wu; Guoping Lu; Keni Zhang; Lehua Pan; Gudmundur S. Bodvarsson (Hydrogeology Journal, 2007)

The Elp3 subunit of human Elongator complex is functionally similar to its counterpart in yeast - Fen Li; Jun Lu; Qiuju Han; Guoping Zhang; Baiqu Huang (Molecular Genetics and Genomics, 2005)

Construction of Double-Copy Glucose Isomerase Gene Engineering Strain of Streptomyces diastaticus by Homologous Recombination - Ying Zhang; Chong Xu; Zhiqiang Lu; Yonghui Yang; Feng Ge; Guoping Zhu; Maikun Teng; Liwen Niu (Current Microbiology, 2002)

Site-Specific Integration of the Double-Mutation Glucose Isomerase (GIG138PG247D) Gene in Streptomyces lividans and Its Stable Expression - Yonghui Yang; Chong Xu; Feng Ge; Zhiqiang Lu; Guoping Zhu; Hui Li; Jun Liao; Liwen Niu; Yuzhen Wang; Mian Wu (Current Microbiology, 2002)

The effects of anomalous snow cover of the Tibetan Plateau on the surface heating - Li Guoping; Lu Jinghua; Jin Bingling; Bu Nima (Advances in Atmospheric Sciences, 2001)

Heterologous Expression of the Single-Mutation Glucose Isomerase (GIG138P) Gene in Streptomyces lividans and Its Genetic Instability - Yonghui Yang; Chong Xu; Feng Ge; Zhiqiang Lu; Guoping Zhu; Hui Li; Jun Liao; Maikun Teng; Liwen Niu; Yuzhen Wang (Current Microbiology, 2001)

Some possible solutions of nonlinear internal inertial gravity wave equations in the atmosphere - Li Guoping; Lu Jinghua (Advances in Atmospheric Sciences, 1996)